A novel impedimetric aptasensor based on AuNPs–carboxylic porous carbon for the ultrasensitive detection of ochratoxin A. Issue 46 (31st May 2017) - Wei, Min; Zhang, Wenyang
Abstract : A novel impedimetric aptasensor based on AuNPs–carboxylic porous carbon for the ultrasensitive detection of OTA. Abstract : A novel aptasensor based on AuNPs–carboxylic porous carbon (cPC) is developed for the ultrasensitive detection of ochratoxin A (OTA) via electrochemical impedance spectroscopy. The prepared AuNPs–cPC, which combines the porous structure of cPC with the good conductivity of AuNPs, is used as an excellent carrier for the immobilization of capture DNA (cDNA), which enhances the loading of the aptamer and amplifies the impedimetric signal. When the target OTA is present, due to the complex effect of the three-dimensional macroporous structure of the AuNPs–cPC on the immobilization of cDNA, hybridization between the aptamer and cDNA and the conformational change of the OTA-aptamer, the OTA-aptamer complex may not be released from the electrode surface, which leads to an increase in the R ct signal. Through optimization of the important parameters, the optimal aptamer concentration of 10 μmol L −1 and optimal incubation time of 9 min are obtained. Under the optimal conditions, the Δ R ct is linearly proportional to OTA concentration in a logarithmic way in the range of 1 × 10 −8 to 0.1 ng mL −1, and the actual limit of detection is 1 × 10 −8 ng mL −1 .